(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Green marketing, also known as environmental or ecological marketing, is gaining momentum as a significant aspect of sustainable business practices. This study explores the evolution, importance, and characteristics of green marketing, highlighting how organizations leverage eco-friendly initiatives to gain competitive advantages. By examining various green marketing strategies—such as energy efficiency, recyclable products, and ethical advertising—the paper identifies factors influencing consumer behavior and highlights exemplary practices by companies globally and in India. The research underscores the gap between consumer attitudes and actions, emphasizing the need for effective strategies to bridge this divide. Recommendations focus on aligning green marketing strategies with consumer expectations, promoting awareness, and fostering innovation for a sustainable future. This study contributes valuable insights for marketers and researchers, enabling the development of impactful green marketing initiatives.